Deficiency of ATF3 facilitates both angiotensin II‐induced and spontaneously formed aortic aneurysm and dissection development by activating cGAS–STING pathway - Yifan Du; Poyi Hu; Xiangchao Ding; Dashuai Wang; Jingjing Luo; Sheng Le; Lingyun Ren; Manhua Chen; Ping Ye; Jiahong Xia (Clinical and Translational Medicine)
Abstract Background Sporadic aortic aneurysm and dissection (AAD) is a critical condition characterised by the progressive loss of vascular smooth muscle cells (VSMCs) and the breakdown of the extracellular matrix. However, the molecular mechanisms responsible for the phenotypic switch and loss of VSMCs in AAD are not fully understood. Methods and results In this study, we employed a discovery‐driven, unbiased approach. This approach encourages us to explore the unknown functions of activating transcription factor 3 (ATF3) rather than merely confirming existing hypotheses, while no assumptions were made about ATF3 prior to the experiments. We ensured the unbiased nature of our assessment by conducting morphological evaluations with two independent observers in a blinded manner. We identified elevated expression of ATF3 in both human sporadic AAD tissues and mouse AAD models. VSMC‐specific ATF3 conditional knockout (Atf3 cKO) mice showed notable enlargement, dissection and rupture in both thoracic and abdominal aortic regions after exposure to Ang II. Interestingly, older Atf3 cKO mice exhibited spontaneous aortic dissections and senescence of the aortic wall. Mechanistically, ATF3 deficiency led to the degradation of P21 through ubiquitination. Impaired DNA repair in VSMCs resulted in micronuclei formation in the cytoplasm, activating the  cyclicGMP‐AMP synthase‐ stimulator of interferon genes (cGAS–STING) pathway and inducing VSMC phenotypic switching and apoptosis. Finally, both pharmacological complementation of P21 function and knockdown of STING expression alleviated ATF3 deficiency‐induced AAD. Conclusions Our study indicates that ATF3 is essential for genomic DNA stability in VSMCs through the P21–cGAS–STING pathway, suggesting that enhancing ATF3 expression in VSMCs could help prevent sporadic AAD. Key points ATF3 deficiency led to degradation of P21 through ubiquitination, which abolished the G1 phase arrest. VSMCs had no time window to repair the damaged DNA, leading to generation of micronuclei in cytoplasm. Cytoplasmic micronuclei facilitating the activation of cGAS–STING pathway, thus inducing the phenotypic switch and apoptosis of VSMCs